The Reality of Tarbiyah, Ta’lim, and Ta’dib in Islamic Education - Susanti, Linna; Al Khoiron, Muhamad Fiqhussunnah; Nurhuda, Abid; Al Fajri, Muhammad (Universitas Muhammadiyah Surakarta, 2023)
Education in Islam is the key for humans to acquire knowledge. And in the concept, similar terms often appear where many people think they have the same meaning, but the essence is different, including the terms tarbiyah, ta'lim, and ta'dib. So the purpose of this study is to describe the nature of Tarbiyah, Ta'lim, and Ta'dib in Islamic Education. The method used is a literature study with qualitative techniques, then analyzed carefully on the relevant contents, and finally concluded with a descriptive. The results of the study show that the emphasis on the term tarbiyah in Islam is focused on guidance and fostering morals, while on the term ta'lim, the emphasis is on conveying complete and correct knowledge. As for ta'dib, the point of emphasis is on the mastery of knowledge that produces charity stability. These three concepts form a unified whole that is interrelated in the educational process, namely Islamic religious education. besides that, it also underlies the goals, methods, educational curriculum, and management that will lead students to become perfect human beings.